Reference ranges for fetal cardiac, ventricular and atrial relative size, sphericity, ventricular dominance, wall asymmetry and relative wall thickness from 18 to 41 gestational weeks. (1st September 2021) - García‐Otero, L.; Soveral, I.; Sepúlveda‐Martínez, Á.; Rodriguez‐López, M.; Torres, X.; Guirado, L.; Nogué, L.; Valenzuela‐Alcaraz, B.; Martínez, J. M.; Gratacós, E.; Gómez, O.; Crispi, F.
ABSTRACT: Objective: To construct nomograms for fetal cardiac, ventricular and atrial relative size and geometry parameters from 18 to 41 weeks' gestation using a low‐risk population of singleton pregnancies. Methods: This was a prospective cohort study of 602 low‐risk singleton pregnancies undergoing comprehensive fetal echocardiography, from 18 to 41 weeks of gestation, to assess fetal cardiac, atrial and ventricular relative size and sphericity, ventricular dominance, wall asymmetry and relative wall thickness. Intra‐ and interobserver measurement reproducibility was evaluated using intraclass correlation coefficients (ICC). In order to construct reference ranges across pregnancy, parametric regressions were tested to model each measurement against gestational age and estimated fetal weight. The measurements evaluated were: cardiothoracic ratio; atrial‐to‐heart area ratios; ventricular‐to‐heart area ratios; cardiac, ventricular and atrial sphericity indices; right‐to‐left basal and midventricular ratios; septal‐to‐free wall thickness ratios; and relative wall thickness. Results: Fetal cardiac, ventricular and atrial morphometry for assessing relative size and geometry could be successfully performed in > 95% of the population, with moderate‐to‐excellent interobserver reproducibility (ICC, 0.623–0.907) and good‐to‐excellent intraobserver reproducibility (ICC, 0.787–0.938). Cardiothoracic ratio and ventricular right‐to‐left ratio showed a modest increase throughout gestation. Atrial‐to‐heart and ventricular‐to‐heart area ratios, atrial sphericity indices and septal‐to‐free wall thickness ratios were constant with gestational age. Left and right ventricular basal sphericity indices showed a tendency to decrease at the end of gestation, while left and right midventricular sphericity indices tended to decrease in the second trimester. The cardiac sphericity index and left and right relative wall thickness showed a modest decrease with gestational age. Nomograms across gestation were constructed for all echocardiographic parameters described. Conclusions: The assessment of cardiac, ventricular and atrial relative size and geometry is feasible and reproducible in the fetus. We provide standardized reference ranges for these parameters throughout gestation, enabling the accurate assessment of cardiac remodeling patterns during fetal life. © 2020 International Society of Ultrasound in Obstetrics and Gynecology